FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PERUSAHAAN - Herianto, Rizka Oktavia; Wibowo, R. Ery (Universitas YPPI Rembang, 2024)
This study aims to examine the effect of profitability, earnings management, leverage, and foreign ownership on CSR disclosure. The research population is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2022-2023. The sample was selected using purposive sampling method, and the number of companies that became the sample was 52 with 104 units of analysis. The data analysis of this research used multiple linear regression. The results showed that profitability variable had a positive effect on CSR disclosure. The leverage variable has a negative effect on CSR disclosure. Earnings management and foreign ownership variables have no effect on CSR disclosure Keywords: Profitability, Earnings Management, Leverage, Foreign Ownership, Disclosure of Corporate Social Responsibility (CSR).